Call Routing Based on a Combination of the Construction-Integration Model and Latent Semantic Analysis: A Full System - Jorge-Botana, Guillermo; Olmos, Ricardo; Barroso, Alejandro (Informatica, 2015)
This study stems from a previous article [1] in which we found that a psycholinguistically motivatedmechanism based on the Construction-Integration (C-I) model [2,3] could be used for call classifiers insystems based on Latent Semantic Analysis (LSA). In it we showed that with this model more robustresults were obtained when categorizing call transcriptions. However, this method was not tested in acontext of calls in audio format, where a voice recognition application would be involved. The mostdirect implication of a voice recognition application is that the text to be categorized may beimpoverished and is subject to noise. This impoverishment normally translates into deletions andinsertions which are semantically arbitrary but phonetically similar. The aim of this study is to describethe behavior of a complete system, with calls in audio format that are transcribed by a voice recognitionapplication using a Stochastic Language Model (SLM), and then categorized with an LSA model. Thisprocess optionally includes a mechanism based on the C-I model. In this study different parameterswere analyzed to assess the automatic router's rate of correct choices. The results show that once againthe model based on C-I is significantly better, but the benefits are more remarkable when the utterancesare long. The paper describes the system and examines both the full results and the interactions in somescenarios. The economy of resources and flexibility of the system are also discussed.